Association between hypertelorism and nonsyndromic oral clefts - Luciano Sólia Nasser; Letízia Monteiro de Barros; Daniella Reis Barbosa Martelli; João Vitor Quadros Tonelli; Mário Sérgio Oliveira Swerts; Hercílio Martelli Júnior (Universidade Estadual de Campinas, 2018)
Hypertelorism is characterized by the increased distance between the orbits, measured from the most medial portion of its inner walls. It represents a signal found in sev eral craniofacial defects, and oral clefts. Nonsyndromic oral clefts (NOC) are the most common orofacial birth defect, occurring in 1 in 500-2,500 live births worldwide. NOC is caused by a complex interplay between environ mental exposures and genetic factors.